1989
DOI: 10.1007/bf00131930
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries and conservation laws of Navier-Stokes equations

Abstract: All the symmetries and conservation laws of Navier-Stokes equations are calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…This was a re-discovery of the symmetries originally discussed in [14]. In fact, as mentioned in the paper where we proposed the BMS/GCA relation [1], the part of the infinite GCA in two dimensions which is the analogue of the restricted BMS 3 algebra (global part of the conformal sub-algebra and the infinite supertranslations) is exactly the symmetry of the Euler equations.…”
Section: An Aside: Non-relativistic Hydrodynamicsmentioning
confidence: 77%
“…This was a re-discovery of the symmetries originally discussed in [14]. In fact, as mentioned in the paper where we proposed the BMS/GCA relation [1], the part of the infinite GCA in two dimensions which is the analogue of the restricted BMS 3 algebra (global part of the conformal sub-algebra and the infinite supertranslations) is exactly the symmetry of the Euler equations.…”
Section: An Aside: Non-relativistic Hydrodynamicsmentioning
confidence: 77%
“…It was found that the GCA could be given an infinite dimensional lift for all space-time dimensions. This also turned out to be related to the symmetries of non-relativistic hydrodynamic equations [5]. In two dimensions, the infinite GCA was shown to arise very naturally from the contraction of two copies of the infinite Virasoro symmetry [6].…”
Section: Introductionmentioning
confidence: 88%
“…Beyond diffeomorphisms, the search in gravity has in general been somewhat limited [15,36], however in the presence of a spacetime isometry, the symmetry group becomes remarkably large [35], particularly for vacuum spacetimes. For symmetries of the Navier-Stokes equations see [31], and with regards to the conformal group [12,32]. In the light of the fluid/gravity correspondence, one may ask whether the symmetries of these systems are linked.…”
Section: Duality In the Context Of Holographymentioning
confidence: 99%
“…In the case of the vacuum-to-vacuum spacetime Ehlers group, the Ernst scalar transforms according to the Möbius map (31). If conjugation of the Ernst scalar is to belong to this map, we must have…”
Section: Generalized Versus Spacetime Ehlersmentioning
confidence: 99%